High density lipoprotein intracellular metabolism in the kidney - Veereswaran, Vasanthi (University of Ottawa (Canada), 2004)
Experiments were undertaken to evaluate the factors that control the re-absorptive salvage of high density lipoproteins (HDL) in the kidney. HDL is readily taken up at the apical surface of polarized human proximal tubule epithelial cells (HKC-8). HKC-8 cells do not degrade HDL apolipoproteins, but instead transport and re-secrete the lipoprotein from the opposite, basolateral surface. Only ∼10% of the HDL lipids taken up are re-secreted, while ∼60% of the internalized HDL proteins are re-secreted. The composition and charge of HDL directly affects their ability to be internalized and transported through HKC-8 cells. HDL-apolipoproteins stimulate the transport of HDL components to the basolateral surface, while HDL-lipids inhibit the process. Enrichment of HDL with phosphatidylinositol (PI) increases HDL negative charge and inhibits its transport and secretion from the basolateral surface. Enrichment with phosphatidylcholine (PC) decreases HDL charge and enhances the transcytosis of HDL. These results show that HDL composition and charge regulate the re-absorptive salvage of HDL apolipoproteins in the kidney by controlling the intracellular metabolism of this lipoprotein. Our data suggest that apical to basolateral transport within proximal tubule cells could serve to recover HDL from the glomerular filtrate and return it back to the circulation. A stimulation of this process may decrease the loss of HDL from the circulation and therefore be anti-atherogenic.
Keywords: Biology, Animal Physiology.; Chemistry, Biochemistry.